The Influence of Leadership and Work Environment on Increasing Employee Performance Through Motivation - Idris, Muhammad; Alwany, Haeranah; Imran, Al (Paradoks : Jurnal Ilmu Ekonomi, 2023)
This investigation aims to determine and assess the impact of leadership, work environment, and motivation on employee performance. The population for this study comprises the entire Makassar Religious Education and Training Center, consisting of 64 individuals: 58 employees and 6 NPASN personnel. The study's sample comprised 64 individuals from the Makassar Religious Education and Training Center, selected using census sampling. The data collection technique consisted of a questionnaire, with each respondent's responses evaluated using a Likert scale. This research uses structural equation modeling (SEM) and SmartPLS 3.0 for data analysis. SEM modeling is an extension of route analysis; using SEM, the causal relationship between exogenous and endogenous factors may be determined in greater detail. Not only can the causal links (direct and indirect) among the observed variables or constructs be recognized using SEM, but also the components that contribute to the production of the construct can be identified. Consequently, the causal relationship between variables or concepts becomes more informative, comprehensive, and precise. According to this study's findings, leadership and the work environment have a significant impact on employee performance. Leadership and the work environment do not affect motivation. Through explanation, leadership, and the work environment, there is no substantial effect on improving employee performance. Moreover, the rationale has a significant impact on employees' performance at the Makassar Religious Education and Training Center. This implies that if employee motivation grows, performance will also increase.